Fenomena Minimnya Tingkat Kejujuran Mahasiswa Dalam Penyelesaian Tugas Akhir di Lingkungan Pendidikan - Komeni, Wirdi Hisroh; Bintang, Cantika Ramadhani; Azhari, Rizka Anugrah; Sari, Elsi Kartika (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
Final Assignment is a scientific work prepared by students in each state or private higher education institution, based on the results of research on a problem which is carried out carefully with the direction of the supervisor. This research examines student dishonesty in completing final assignments. In this case, honesty should be a principle that must be adhered to by students. However, until now, there is still the problem of student dishonesty. This research aims to determine the forms of academic honesty behavior when facing exams among students and what are the reasons underlying academic honesty and dishonesty behavior during exams among students. As information from the results of observations, interviews and documents that support this research. This research data analysis method consists of three steps using the Miles and Huberman model of data reduction, data presentation, drawing conclusions, and validation. The results of this research. The results of this research need to know what factors cause the low level of honesty of students in completing final assignments and solutions and roles are needed by educational institutions in dealing with this problem in order to reduce the number of students who act dishonestly in writing scientific work.